Transformasi Kehidupan Rohani Jemaat dalam Era Digital: Implikasi Digital Religion terhadap Pendidikan Agama Kristen - Purwonugroho, Daniel Pesah (Ritornera - Jurnal Teologi Pentakosta Indonesia, 2025)
This paper is designed to explore the transformation of church spiritual life in the digital era and the implications of digital religion for Christian religious education. Digital religion is a phenomenon that arises due to the rapid development of technology. Digital religion presents religious interactions in the digital space. Digital religion also changes the spiritual life of the congregation where worship celebrations, transmission of religious messages and pastoral care also experience significant changes. Through a descriptive qualitative approach, the author tries to explore how digital religion has implications for Christian religious education including transforming the spiritual life of the congregation. The author argues that churches, church leaders and Christian educators need to prepare themselves to equip congregants and learners about this digital religion phenomenon. This paper offers a practical attitude for church leaders and Christian educators to prepare themselves in facing digital religion so that the spiritual life of the congregation can be optimized properly.AbstrakTulisan ini dirancang untuk menelusuri transformasi kehidupan rohani jemaat dalam era digital dan implikasi digital religion terhadap pendidikan agama Kristen. Digital religion merupakan fenomena yang muncul dikarenakan perkembangan teknologi yang sangat pesat. Digital religion menghadirkan interaksi-interaksi keagamaan di ruang digital. Digital religion juga mengubah kehidupan rohani jemaat dimana perayaan ibadah, transmisi pesan keagamaan dan pastoral juga mengalami perubahan yang signifikan. Melalui pendekatan kualitatif deskriptif, penulis mencoba untuk mengeksplor bagaimana digital religion memberikan implikasi terhadap pendidikan agama Kristen termasuk mentransformasikan kehidupan rohani jemaat. Penulis menyatakan bahwa gereja, pemimpin gereja dan pendidik Kristen perlu mempersiapkan diri untuk memperlengkai jemaat dan peserta didik tentang fenomena digital religion ini. Tulisan ini menawarkan sebuah sikap praktis bagi pemimpin gereja dan pendidik Kristen untuk mempersiapkan diri dalam menghadapi digital religion agar kehidupan rohani jemaat dapat teroptimalisasi dengan baik.